'I didn't expect teaching to be such a huge part of nursing': A follow-up qualitative exploration of new graduates' teaching activities. (September 2018) - McKenna, Lisa; Irvine, Susan; Williams, Brett
Abstract: Background: Teaching has long been recognised as an important role for nurses. In addition, much has also been written about new graduates' transitions to professional practice. However, the role of new graduates in teaching is unclear, and at what point they are required to teach others as part of their practice. Objectives: To explore the teaching activities undertaken by new nursing graduates, and their readiness for this role following a semester-long education subject in their undergraduate degrees. Design: A qualitative descriptive design Settings: All participants were undertaking graduate nurse programs and working in different hospitals across Melbourne, Australia. Five were working in public hospitals, and one in a private hospital. Participants: Six graduate nurses who had completed the education subject at one Australian university and were between four and six months into their graduate year program. Methods: Semi-structured interviews guided by key questions were conducted by telephone. Transcripts were analysed using thematic analysis. Results: Three themes emerged: expectations and the nature of teaching, nature of learners, and attitudes to teaching role. All participants were engaged in some teaching activity early in their graduate programs. This included students of nursing and other disciplines, and qualified staff, as well as patients and their families. Participants reported feeling more confident and better prepared for their roles having completed the education subject than those of their peers, educated at other universities, who had not covered such content. Conclusions: New graduates are required to teach others, both formally and informally, early after registration. This requirement of professional practice is assisted by the inclusion of an education subject embedded in the undergraduate nursing degree. Highlights: New graduate nurses are required to teach others early in their graduate years. Graduate nurses are required to teach many different learners, including students of other health professions. Undergraduate teaching and learning experiences can assist graduates to perform the teaching aspects of their roles.